Honos alit artes. Studi per il settantesimo compleanno di Mario Ascheri. II. Gli universi particolari Città e territori dal medioevo all'età moderna - Paola Maffei (Reti Medievali E-Book, 2014)
The researches accounted in the volume, being reported by historians who had different vocations, illustrate various aspects of medieval and modern history (laws, economy, society, church and civil institutions, architecture, art, urban planning); they are focused on single town realities and limited geographical-political areas. Among these, particular attention ought to be given to the city of Siena and its territory, which constitute one of the centres of interest for the illustrious scholar to whom is dedicated the series of four volumes, which the present also belongs to.